Household Solid Waste Recycling: A Comparison Between Malaysia and Singapore from the Legal Perspective - Wan Siti Adibah Wan Dahalan; Zulkifli Mohd Nopiah; Intan Nadia Ghulam Khan (Medwell Journals, 2024)
This study presents an evaluation on household solid waste recycling legal provisions in Malaysia and Singapore. Solid waste has become a central issue particularly in developing countries. The generation of solid waste has increased thus, becoming one of the major causes of pollutions prevailing particularly in developing countries. The sustainable and effective solid waste management is important in order to mitigate or reduce solid wastes negative impacts on the environment. One of the issues relating to solid waste management in developing countries including Malaysia is the low recycling rate. Recycling is one of the options in 3R (Reduce, Reuse and Recycle). Singapore, on the other hand has successfully established a sound material recycling society in the country. This study evaluates several aspects of solid waste management in Malaysia and Singapore, namely, solid waste management practiced in both countries, legislations regulating solid waste management and specific provisions on household solid waste recycling as contained in statutes and regulations in both countries. The finding indicates that landfill is the last option of the waste disposal method in Singapore. In Singapore, the focus is on waste minimization and recycling. Meanwhile, it is discovered that Malaysia prefers landfill over other methods of waste disposal. Similarities could be seen in terms of both countries commitments to effectively manage solid waste through the enactment of laws particularly legislations to regulate household solid waste recycling. Nevertheless, the systematic waste collection and recycling strategies would help Malaysia in order to enhance the household solid waste recycling in Malaysia.